Community Pharmacist Utilization of Legislation That Allows Impact on the Opioid Crisis in the State of Minnesota: A Mixed-Methods Approach. (December 2020) - Palombi, Laura; Hawthorne, Amanda N.; Lunos, Scott; Melgaard, Kelsey; Dahly, Ashley; Blue, Heather
Background: As opioid overdose deaths climb, legislation supporting pharmacists in developing their role to address the crisis has expanded. Although Minnesota pharmacists are encouraged to utilize opiate antagonist, syringe access and authorized collector legislation, the use patterns of these tools are unknown. Methods: A mixed-methods approach was used to survey 8405 Minnesota-licensed pharmacists on their practices related to the opioid crisis. An analysis of community pharmacist utilization of opioid-related legislation was conducted. Results: The majority (88.64%) of respondents indicated that they had not dispensed naloxone in the past month using a protocol; 59.69% reported that they had not dispensed naloxone by any method in the past month. Over sixty percent (60.61%) of respondents agreed they are comfortable with dispensing syringes and would dispense noninsulin syringes in their pharmacy under the statewide Syringe Access Initiative; 25.86% reported that they are not comfortable dispensing syringes. The majority (78.64%) of respondents reported that they do not participate in collecting unwanted pharmaceuticals. Conclusion: While pharmacists have the potential to play a key role in efforts focused on addressing the opioid crisis through harm reduction strategies, this role and the use of supporting legislation is currently underutilized in the state of Minnesota.